Talking about Leaving Revisited Persistence, Relocation, and Loss in Undergraduate STEM Education - Seymour, Elaine; Hunter, Anne-Barrie (Springer International Publishing : Imprint: Springer, 2019)
XXII, 528 p. 64 illus., 47 illus. in color.